Efficient oxidation and rational reduction of long carbon nanotubes for multifunctional superhydrophobic surfaces. (February 2020) - Yang, Hye Jin; Cho, Joon Young; Kim, Jung Hoon; Kim, Ho Young; Lee, Jae-Won; Wang, Ji Won; Kwak, Ji Hye; Jung, Sunshin; Park, Jong Hwan; Jeong, Hee Jin; Jeong, Seung Yol; Seo, Seon Hee; et al.
Abstract: The inclusion of conducting nanomaterials in superhydrophobic surfaces can widen their potential applications in terms of Joule heating, electromagnetic interference shielding, oil/water separation, and self-cleaning. Here, we demonstrate the fabrication of multifunctional superhydrophobic surfaces using dispersant-free conducting inks containing highly oxidized long multiwalled carbon nanotubes (Ox-LMWCNTs). Superhydrophobic surfaces with a high water contact angle (WCA) (>150°) were realized by deposition of a perfluorosilane sol and silica nanoparticle mixture solution onto the Ox-LMWCNT surface and subsequent thermal treatment. Importantly, the electrical conductivities of the Ox-LMWCNT films were dramatically increased from 78 S/m to more than 2000 S/m by thermal deoxygenation, even at low temperatures (<200 °C) in ambient air. The superhydrophobic LMWCNT films showed high electrical conductivity of more than 1000 S/m following thermal treatment at 150 °C in ambient air. These electrically conducting and self-cleaning surfaces also showed fast heating behavior when a direct current voltage was applied to the film. Moreover, sequential deposition of the LMWCNT and perfluorosilane sol solutions on a metal mesh produced an oil/water separation filter owing to the oleophilic properties of the LMWCNTs. As they are easily dispersed in solution and can undergo efficient thermal deoxygenation, Ox-LMWCNTs are promising for the realization of multifunctional surfaces. Graphical abstract: Conductive and superhydrophobic films with multi-functionality are fabricated by using efficiently oxidized long multi-walled carbon nanotubes. Highly oxidized carbon nanotubes with less permanent defect can be thermally deoxygenated in ambient air. Dispersant-free carbon nanotube inks were utilized to fabricate superhydrophobic film heaters and oil/water separation filters. Image 1